2020
DOI: 10.3390/math8101658
|View full text |Cite
|
Sign up to set email alerts
|

Two Nested Limit Cycles in Two-Species Reactions

Abstract: We search for limit cycles in the dynamical model of two-species chemical reactions that contain seven reaction rate coefficients as parameters and at least one third-order reaction step, that is, the induced kinetic differential equation of the reaction is a planar cubic differential system. Symbolic calculations were carried out using the Mathematica computer algebra system, and it was also used for the numerical verifications to show the following facts: the kinetic differential equations of these reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Shabunin et al [6] discussed limit cycle analysis and chaotic behavior for a chemical reaction system under an external periodic force. Nagy et al [7] reported two nested type limit cycles for a two-species chemical reaction model.…”
Section: Introductionmentioning
confidence: 99%
“…Shabunin et al [6] discussed limit cycle analysis and chaotic behavior for a chemical reaction system under an external periodic force. Nagy et al [7] reported two nested type limit cycles for a two-species chemical reaction model.…”
Section: Introductionmentioning
confidence: 99%